The relationship of cumulative psychosocial adversity with antepartum depression and anxiety. Issue 10 (9th August 2021) - Barrios, Yasmin V.; Maselko, Joanna; Engel, Stephanie M.; Pence, Brian W.; Olshan, Andrew F.; Meltzer‐Brody, Samantha; Dole, Nancy; Thorp, John M.
Abstract: Background: Exposure to multiple psychosocial risk factors may increase vulnerability for mental health conditions during pregnancy. This analysis examined the relationship of a novel psychosocial adversity index with the co‐occurrence and persistence of depression and anxiety throughout pregnancy. Methods: This cross‐sectional analysis included 1797 pregnant women screened in the second/third trimesters for depression and anxiety symptoms and for eight contextual and individual psychosocial factors. The factors were summed to create a psychosocial adversity index; reporting four or more factors indicated high adversity. Elevated symptoms in both trimesters indicated persistent depression/anxiety and elevated symptoms at the same trimester indicated comorbid symptoms. The associations between the psychosocial adversity index and mental health were estimated. Results: Compared with a low psychosocial adversity index, women reporting a high level of psychosocial adversities had 2.06 (95% confidence interval [CI]: 1.51–2.82) times higher adjusted odds of only depressive or anxiety symptoms, and 5.57 (95% CI: 3.95–7.85) times higher adjusted odds of comorbid symptoms. The associations for persistent symptoms were of similar direction and magnitude. Conclusion: High psychosocial adversity was associated with persistent and comorbid depressive symptoms and anxiety during pregnancy. Assessing psychosocial adversity can help identify women at increased risk who would benefit from tailored mental health interventions.